Super-resolution Reconstruction of Noisy Video Image Based on Sparse Representation Algorithm - Zhang, Tierui; Li, Dandan; Cai, Yanxia; Xu, Yanyan (Informatica, 2024)
This paper has been retracted at the authors' request.